A Retrospective Study on Previously Untreated Non-metastatic Breast Cancer Patients at a Tertiary Care Hospital (Journal of Armed Forces Medical College, Bangladesh, 2023)
Introduction: The combination of adoxorubicin and cyclophosphamide (AC) followed by a taxane (Docetaxel or Paclitaxel) and epirubicin and cyclophosphamide (EC) followed by a taxane (Docetaxel or Paclitaxel) is a standard regimen for breast cancer patients. In this study, we compared the three-year overall survival (OS) and progression free survival (PFS) of a patient with previously untreated non-metastatic breast cancer patients.  Objectives: To find out the overall survival and progression free survival among previously untreated non-metastatic breast cancer patients after standard chemotherapy. Methods: Fifty-six patients received four cycles of doxorubicin at a dose of 60mg/m2 and cyclophosphamide at a dose of 600 mg/m2 followed by four cycles of paclitaxel at a dose of 175mg/m2. Thirteen patients received AC followed by four cycles of docetaxel at a dose of 75mg/m2. Twenty-one patients received four cycles of epirubicin (75mg/m2) and cyclophosphamide (600mg/m2), followed by four cycles of paclitaxel (175mg/m2). Twelve patients were given EC followed by four cycles of docetaxel (75mg/m2).Results: The four groups of patients had similar characteristics. Overall survivalafter three years was 92% in AC followed by paclitaxel, 98% in AC followed by docetaxel, 95% and 97% in EC followed by paclitaxel and docetaxel respectively. One year of PFS in AC followed by paclitaxel and docetaxel was 98% and 100% respectively whereas in EC followed by paclitaxel and docetaxel were 98% and 98% respectively. The four arms had 96%, 98%, 97% and 96% PFS after two years respectively. This research also revealed that four chemotherapy regimens had three-year survival rates of 93%, 98%, 93% and 96% respectively.Conclusion: AC or EC followed by taxane regimens well suitable regimens for the population of patients with previously untreated non-metastatic breast cancer patients. The findings show the need for continued observation as well as taking into account the treatment of other patients throughout different periods.JAFMC Bangladesh. Vol 18, No 2 (December) 2022: 11-14